Lack of myotubularin (MTM1) leads to muscle hypotrophy through unbalanced regulation of the autophagy and ubiquitin‐proteasome pathways. Issue 8 (21st May 2013) - Al‐Qusairi, Lama; Prokic, Ivana; Amoasii, Leonela; Kretz, Christine; Messaddeq, Nadia; Mandel, Jean‐Louis; Laporte, Jocelyn
Abstract : Mutations in the phosphoinositide phosphatase myotubularin (MTM1) results in X‐linked myotubular/centronuclear myopathy (XLMTM), characterized by a severe decrease in muscle mass and strength in patients and murine models. However, the molecular mechanism involved in the muscle hypotrophy is unclear. Here we show that the IGF1R/Akt pathway is affected in Mtm1 ‐deficient murine muscles, characterized by an increase in IGF1 receptor and Akt levels in both the presymptomatic and symptomatic phases. Moreover, up‐regulation of atrogenes was observed in the presymptomatic phase of the myopathy, supporting overactivation of the ubiquitin‐proteasome pathway. In parallel, the autophagy machinery was affected as indicated by the increase in the number of autophagosomes and of autophagy markers, such as LC3 and P62. However, phosphorylation of FOXO3a and mTOR were abnormal at late but not at early stages of the disease, suggesting that myotubularin acts both upstream in the IGF1R/Akt pathway and downstream on the balance between the autophagy and ubiquitin‐proteasome pathways in vivo . Adeno‐associated virus‐mediated delivery of Mtm1 into Mtm1 ‐null muscles rescued muscle mass and normalized the expression levels of IGF1 receptor, the ubiquitin‐proteasome pathway, and autophagy markers. These data support the hypothesis that the unbalanced regulation of the ubiquitin proteasome pathway and the autophagy machinery is a primary cause of the XLMTM pathogenesis.—Al‐Qusairi, L., Prokic, I., Amoasii, L., Kretz, C., Messaddeq, N., Mandel, J.‐L., Laporte, J. Lack of myotubularin (MTM1) leads to muscle hypotrophy through unbalanced regulation of the autophagy and ubiquitin‐proteasome pathways. FASEB J. 27, 3384–3394 (2013). www.fasebj.org